Optimizing aspirin dose for colorectal cancer patients through deep phenotyping using novel biomarkers of drug action - Patrignani, Paola; Tacconelli, Stefania; Contursi, Annalisa; Piazuelo, Elena; Bruno, Annalisa; Nobili, Stefania; Mazzei, Matteo; Milillo, Cristina; Hofling, Ulrika; Hijos-Mallada, Gonzalo; Sostres, Carlos; Lanas, Angel (Frontiers in Pharmacology, 2024)
Background. Low-dose aspirin's mechanism of action for preventing colorectal cancer (CRC) is still debated, and the optimal dose remains uncertain. We aimed to optimize the aspirin dose for cancer prevention in CRC patients through deep phenotyping using innovative biomarkers for aspirin's action. Methods. We conducted a Phase II, open-label clinical trial in 34 CRC patients of both sexes randomized to receive enteric-coated aspirin 100 mg/d, 100 mg/BID, or 300 mg/d for 3±1 weeks. Biomarkers were evaluated in blood, urine, and colorectal biopsies at baseline and after dosing with aspirin. Novel biomarkers of aspirin action were assessed in platelets and colorectal tissues using liquid chromatography-mass spectrometry to quantify the extent of cyclooxygenase (COX)-1 and COX-2 acetylation at Serine 529 and Serine 516, respectively. Results. All aspirin doses caused comparable % acetylation of platelet COX-1 at Serine 529 associated with similar profound inhibition of platelet-dependent thromboxane (TX)A2 generation ex vivo (serum TXB2) and in vivo (urinary TXM). TXB2 was significantly reduced in CRC tissue by aspirin 300 mg/d and 100 mg/BID, associated with comparable % acetylation of COX-1. Differently, 100 mg/day showed a lower % acetylation of COX-1 in CRC tissue and no significant reduction of TXB2. Prostaglandin (PG)E2 biosynthesis in colorectal tumors and in vivo (urinary PGEM) remained unaffected by any dose of aspirin associated with the variable and low extent of COX-2 acetylation at Serine 516 in tumor tissue. Increased expression of tumor-promoting genes like VIM (vimentin) and TWIST1 (Twist Family BHLH Transcription Factor 1) vs. baseline was detected with 100 mg/d of aspirin but not with the other two higher doses. Conclusions. In CRC patients, aspirin 300 mg/d or 100 mg/BID had comparable antiplatelet effects to aspirin 100 mg/d, indicating similar inhibition of the platelet's contribution to cancer. However, aspirin 300 mg/d and 100 mg/BID can have additional anticancer effects by inhibiting cancerous tissue's TXA2 biosynthesis associated with a restraining impact on tumor-promoting gene expression. EUDRACT number: 2018-002101-65; ClinicalTrials.gov Identifier: NCT03957902